Arbejdsprøve med smaa selvrensende Tærskeværker til Hestekraft paa Askov 1905. - Birk, C. V. (Tidsskrift for Landøkonomi, 2018)
Arbejdsprøve med smaa selvrensende Tærskeværker til Hestekraft paa Askov 1905.